Penguatan Nilai Toleransi melalui Pembelajaran Pendidikan Agama Islam Berbasis Diferensiasi pada Kelas Inklusif: Studi Kasus di SD Negeri 33 Pangkalpinang - Septia Fahiroh; Auliani Oktara; Fitri Oviyanti; Leny Marlina (WISE Pendidikan Indonesia, 2026)
Low tolerance among students in inclusive classrooms is reflected in limited respect for differences in ability and learning backgrounds, while Islamic Religious Education (PAI) has not always adequately accommodated student diversity. This study aimed to analyze the strengthening of tolerance values through differentiated PAI instruction in an inclusive classroom at SD Negeri 33 Pangkalpinang. The study was grounded in differentiated instruction, moral development, and rights-based inclusive education perspectives. A qualitative case-study design was employed, involving the PAI teacher, school principal, and students selected through purposive sampling. Data were collected through classroom observations, in-depth interviews, and documentation and were analyzed interactively through data reduction, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation and member checking. The findings revealed that differentiated PAI instruction strengthened tolerance through needs-responsive planning, heterogeneous group learning, peer support, reflective activities, and teacher modeling. These practices enabled students with diverse learning profiles to participate meaningfully, develop empathy, cooperate, and respect differences. The findings indicate that differentiated PAI instruction functions not only as an inclusive pedagogical strategy but also as a mechanism for character formation by structuring equitable participation and social interaction among students. Therefore, differentiated PAI instruction offers a relevant pedagogical pathway for integrating inclusive education with tolerance development, while future studies should employ more systematic documentation and standardized measures of tolerance.